196k views
0 votes
Rewrite the equation by completing the square x^2-2x+1=0

User Sunsean
by
6.2k points

1 Answer

3 votes

Answer:

(x-1)^2=0#

Step-by-step explanation:

#x^2-2x+1=0#

Let's start by subtracting #1# from both sides so that the #x# terms are isolated:

#x^2-2x=-1#

Now, let's compute #(b/2)^2# and add it to both sides of the equation:

#(b/2)^2=(-2/2)^2=1#

#x^2-2x+1=-1+1#

Let's factorize the left hand side and simplify:

#(x-1)(x-1)=0#

#(x-1)^2=0#

User Linktoahref
by
6.3k points